Implementasi Simulasi Data Logging Berbasis Iot Untuk Monitoring Kendaraan Dengan Android - Muh.Sabri; Angriawan, Ryan; Hariyeni (CV. SINAR HOWUHOWU, 2026)
The development of Internet of Things (IoT) technology has created significant opportunities for the implementation of real-time and integrated vehicle monitoring systems. This study aims to implement an IoT-based data logging simulation to monitor vehicle conditions and activities through an Android-based platform. The developed system utilizes sensors as sources of vehicle data, a microcontroller for data processing, and internet connectivity as the medium for transmitting data to a server. The collected data include vehicle location, speed, and status, which are automatically stored in a database as data logs and displayed through an Android application using an informative and user-friendly interface. The research methodology consists of system requirement analysis, hardware and software architecture design, implementation of the IoT system simulation, and functional testing of the system. The simulation is conducted to ensure that the processes of data acquisition, transmission, storage, and visualization operate according to the designed system workflow. The results indicate that the IoT-based data logging simulation system is capable of performing real-time vehicle monitoring with good data accuracy and stable Android application performance. Furthermore, the system facilitates remote vehicle monitoring and provides historical data records that can be utilized for further analysis. Therefore, the implementation of an IoT-based data logging simulation for vehicle monitoring using Android can serve as an effective and efficient alternative solution to support modern vehicle monitoring systems. This study is expected to serve as a reference for future research on IoT-based vehicle monitoring systems.